Characteristics of Flying Height for Time Independent Sub Ambient Pressure Slider Head - เจริญ, ณัฎฐปกรณ์; พานิชกรณ์, เจษฎา; วงษ์สีดาแก้ว, ขนิษฐา (Srinakharinwirot University Engineering Journal, 2019)
This paper describes the characteristics of flying height time independent sub ambient pressure slider head. The modified Reynold equation was formulated for air lubrication with the effect of molecular slip. Finite difference method, Newton-Raphson method and multigrid technique was implemented to obtain air pressure distribution and flying height of the slider. The simulation results show that the film pressure rapidly increases at the trailing edge region. The flying height decreases with increasing air pressure when increasing load. The flying height increases when increasing velocity of disk. For increasing of air inlet temperature, the flying height increases. The appropriate of slider head groove depth is 2 m.